Examining belief adjusment model and framing effect on the audit materiality level decision making - Febriyani Sarwindah; Almilia, Luciana Spica; Mustafida, Nurul (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
The purpose of this study is to examine whether or not there is a difference in the decision-making of external auditors in determining the level of audit materiality between participants who get good news followed by bad news and those who get bad news information sequences (bad news) followed by good news (good news) with a step-by-step and end-of-sequence information presentation pattern in the positive frame or negative frame. The research method used in the research is the mixed design experiment method (between and within the subject) which manipulates the independent variables of the order of evidence (good news followed by bad news and bad news followed by good news) and framing effect (positive frame or negative frame) in the presentation pattern Step by Step and End of Sequence. Participants in this study were 150 students of the Bachelor of Accounting study program at Hayam Wuruk Perbanas Surabaya University with 300 experiment data. This study uses the normality test and the Kruskall-Wallis H test. The results of this study indicate that the Step-by-step presentation pattern can cause a recency effect when receiving information with a sequence of evidence of good news followed by bad news and bad news followed by good news both in the series, with the positive or negative frame, and the results obtained if the information is presented with an End of Sequence presentation pattern with information and a sequence of evidence of good news followed by bad news or bad news followed by good news there is no difference (no order effect) either in the framing effect (positive frame and negative frame).